Hyperbaric Oxygen Therapy for Mumps-Associated Outer Retinitis with Frosted Branch Angiitis. (19th May 2022) - Sayadi, Jihene; Ksiaa, Imen; Malek, Ines; Ben Sassi, Raja; Essaddam, Leila; Khairallah, Moncef; Nacef, Leila
ABSTRACT: Purpose: To describe a case of outer retinitis with frosted branch angiitis associated with mumps infection treated with hyperbaric oxygen (HBO) therapy. Methods: Observational case report Case report: A four-year-old boy with bilateral blindness was diagnosed with necrotizing outer retinitis with frosted branch angiitis associated with serologically confirmed mumps virus infection. He was treated with HBO therapy. Visual acuity subsequently improved to 20/40 in the right eye and to 20/320 in the left eye. Sequential follow-up optical coherence tomography examinations showed progressive recovery of the outer retinal layers in the right eye. Conclusion: HBO therapy appears to be a feasible and safe treatment that might improve the anatomical and functional outcome in patients with mumps retinitis.